Omega-3 Polyunsaturated Fatty Acids and the Resolution of Inflammation: Novel Therapeutic Opportunities for Aortic Valve Stenosis? - Artiach, Gonzalo; Bäck, Magnus (Frontiers in Cell and Developmental Biology, 2020)
Inflammation is well-established in cardiovascular disease, including valvular heart disease. Inflammation is a key process in the fibrosis and calcification of the aortic valve leaflets, which ultimately clinically manifest as aortic valve stenosis characterized by valve dysfunction and cardiac obstruction. In the absence of pharmacological treatment, either surgical or transcatheter aortic valve replacement is currently the only available therapeutic strategy for patients with severe aortic valve stenosis. Omega-3 polyunsaturated fatty acids, which exert beneficial effects in several cardiovascular diseases, serve as the substrate for several bioactive lipid mediators that regulate inflammation. Recent findings point to beneficial effects of omega-3 fatty acids in cardiac valves, being inversely associated with aortic valve calcification and contributing to the resolution of valvular inflammation by means of the proresolving mediator resolvin E1 and downstream signaling through its receptor ChemR23.